Feminization of Sri Lankan Doctors and Key Specialties: 2000 to 2020 - Silva, Dileep De; Adikari, Pamila; Rubasinghe, Mihiri S; Seneviratne, Udeni L (Journal of Indonesian Health Policy and Administration, 2023)
The study focused on the feminization of Sri Lankan generalist doctors in all major and selected minor specialties between 2000 and 2020. The study analyzed all relevant documents by exploring Sri Lanka's male-to-female doctor and specialist ratio over 20 years. This was determined by analyzing state medical faculty records from 1990 to 2020. For better clarity, the researchers analyzed the gender ratio changes in every five-year block from 1990 to 2020. Focus groups filled PGIM's gender data fields. Five-year medical students surged from 43% to 63% between 1990 and 2020. Linear trend analysis predicts 68% of female medical students by 2025 and 72% by 2030. This study simulated generalist doctors with medical students. Until recently, men dominated medicine, surgery, obstetrics, and pediatrics. Female specialists have increased in all fields over the past 20 years. The feminization of medical doctors challenges national human resource policies and health sector reforms. They emphasize gender-sensitive health workforce planning that considers a country's economic development and healthcare system. Sri Lankan health policymakers should consider gender dynamics in national health HR planning for the next decade.